Pseudorandom Number Generator Based on Linear Feedback Shift Register Algorithm - Aliyeva, I.N. (Herald of Azerbaijan Engineering Academy, 2023)
In the article, the analysis of various schemes of pseudorandom number generators is carried out and their main shortcomings are recorded. Taking into account the identified shortcomings, the principle scheme of the pseudo-random number generator based on the linear feedback shift register algorithm is proposed to ensure the confidentiality of transmitted data in communication and control systems. The work algorithms of the control and controlled registers, which are the main parts of the proposed device and are implemented on the basis of PIC16F84A microcontrollers, are shown. At the end of the article, the general view of the device implemented based on the proposed principle scheme is reflected.